Promotion of breasfeeding on human milk banks of Rio De Janeiro - Maria Bertilla Lutterbach Riker Branco; Valdecyr Herdy Alves; Diego Pereira Rodrigues; Rosangela de Mattos Pereira de Souza; Amanda Fernandes do Nascimento da Cruz; Tuâny Figueiredo Marinho (Universidade Federal de Santa Maria, 2015)
Aim: to describe the care practice of health professionals to support breastfeeding in Human Milk Banks of Rio de Janeiro. Method: descriptive, exploratory and qualitative study in five Human Milk Banks, with participation of twenty five health professionals working on health care services. The data were collected through semistructured interviews and submitted to content analysis in the thematic mode. Results: three categories were found: "An orientation to the work at a Human Milk Bank: a space to conduct suitably breastfeeding", "The use of the Human Milk Bank to promote the breastfeeding at home" and "The media as a promotional tool of breastfeeding within the Human Milk Bank". Conclusion: the promotion of breastfeeding in Human Milk Banks is performed by health care professionals working in partnership with the media and the family, essential elements for its success